Design, synthesis, spectral analysis, and biological evaluation of Schiff bases with a 1,3,4-thiadiazole moiety as an effective inhibitor against bacterial and fungal strains - Malak, Sajid Ajit; Rajput, Jamatsing Dabarsing; Sharif, Mustakim (European Journal of Chemistry, 2023)
Many distinct natural and pharmaceutical items include the well-known heterocyclic nucleus 1,3,4-thiadiazole. Ten Schiff bases of 1,3,4-thiadiazole derivatives have been synthesized using equimolar amounts of 5-styryl-1,3,4-thiadiazol-2-amine and substituted acetophenones in the catalytic amount of ethanol. The synthesized derivatives of Schiff’s bases were characterized by FT-IR, 1H NMR, 13C NMR, and mass spectroscopy. The 1,3,4-thiadiazole Schiff’s bases (RM-1 to RM-10) were tested for their in vitro antimicrobial activity against Pseudomonas aeruginosa, Escherichia coli, Bacillus subtilis, Aspergillus niger, Aspergillus fumigatus, Aspergillus flavus using the disc diffusion method. The 1,3,4-thiadiazole Schiff bases showed strong antibacterial activity against bacterial and fungal species, however, their activity was noticeably less effective than that of the evaluated conventional antibiotics.